Psychisme et opérativité chez Maître Eckhart - Yves Meessen (Recherches Germaniques)
By underlining the correlativity of the soul and God, Jung has put his finger on a fundamental point of Master Eckhart’s mysticism. The choice to maintain the link between psychology and logic allowed Eckhart to resist the semantisation of theology. The discourse on God is performative. The sermons are constructed as an invitation to experience divine operativity, which is irreducible to any representation. Through the Eckhartian distinction between God and Deity, Jung recognises that any psychological production of a personification of God is already derived from an unconscious activity from which the soul draws its dynamism. From this, an ethical path of becoming-self emerges. Where Jung speaks of individuation, we should rather speak of personalisation in Eckhart’s case, because becoming is a process of dedevelopment, as a conformation to Christ. Between the two, it is a question of determining whether the original disposition of the mind in its primitive energetic conception is immediately opposed to a historical revelation or, on the contrary, one can corroborate the other.